2019
DOI: 10.1007/s10068-019-00626-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory effects of an ethanol fraction from the Schisandra chinensis baillon hot water extract fermented using Lactobacilius paracasei subsp. tolerans

Abstract: Waste management is a major part of the food industry. The present study was designed to utilize the discarded byproduct of Schisandra chinensis Baillon. The antioxidant and anti-inflammatory effects of a 30% ethanol fraction (RPG-OM-30E) from the fermented hot water extraction of the Schisandra chinensis Baillon byproduct were investigated using RAW 264.7 cells and zebrafish larvae. RPG-OM-30E reduced lipopolysaccharide (LPS)-induced nitric oxide production in the RAW 264.7 cells. Additionally, RPG-OM-30E inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Studies have found that Tg( mpx :EGFP) zebrafish (neutrophils are specifically labelled with green fluorescent protein) can be used to observe inflammatory responses [ 25 ], and we observed inflammation in Tg( mpx :EGFP) zebrafish. The five-day old Tg( mpx :EGFP) zebrafish larvae were randomly divided into five groups: control group, AS group, 0.1 mg/L DHWE group, 1 mg/L DHWE group, and 10 mg/L DHWE group.…”
Section: Methodsmentioning
confidence: 54%
“…Studies have found that Tg( mpx :EGFP) zebrafish (neutrophils are specifically labelled with green fluorescent protein) can be used to observe inflammatory responses [ 25 ], and we observed inflammation in Tg( mpx :EGFP) zebrafish. The five-day old Tg( mpx :EGFP) zebrafish larvae were randomly divided into five groups: control group, AS group, 0.1 mg/L DHWE group, 1 mg/L DHWE group, and 10 mg/L DHWE group.…”
Section: Methodsmentioning
confidence: 54%
“…These results are in concordance with Liu et al (2016), who assessed the anti‐inflammatory properties of Lactobacillus brevis K65 on RAW 264.7 cells. Similarly, Choi and Moon (2020), Jia et al (2021), Liu, Tsai, and Pan (2018), and Yang et al (2019), using RAW 264.7 cells, have distinguished that Lactobacillus paracasei had anti‐inflammatory properties. Hence, this outcome indicates that it could contribute to a profound anti‐inflammatory response's role in the development and progression of inflammatory conditions.…”
Section: Resultsmentioning
confidence: 95%
“…Inflammation is a complex immune response of the body to injury [ 28 ]. Inflammatory response starts as an acute reaction, whereas unresolved immune activation causes chronic inflammation by affecting local tissues or systemic immunity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%